Evaluasi dan Strategi Pengembangan Desa Wisata dengan Importance-Performance Analysis (IPA) - Achsa, Andhatu; Verawati, Dian Marlina; Hutajulu, Dinar Melani (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this research is to evaluate and determine the right strategy for the development of tourist villages in the Borobudur Temple area. The research emphasizes the aspect of customer satisfaction as the main study material and performs an analysis using the Importance-Performance Analysis method. The results show that there are indicators that become achievement priorities, top priorities, low priorities and excessive priorities in each tourist village. From the results of the evaluation, a strategy was set for the Karanganyar Tourism Village which leads to the improvement of human resources with the addition of management skills, the Tuksongo Tourism Village the need for renewal of accessibility which should also be supported by the local government, and the Wanurejo Tourism Village the need for the application of information systems on social media and the website to support the tourists in seeing the tours offered by the village.